Ventilator modes and settings during non-invasive ventilation: effects on respiratory events and implications for their identification. Issue 2 (14th October 2010) - Rabec, Claudio; Rodenstein, Daniel; Leger, Patrick; Rouault, Sylvie; Perrin, Christophe; Gonzalez-Bermejo, Jésus
Abstract : Compared with invasive ventilation, non-invasive ventilation (NIV) has two unique characteristics: the non-hermetic nature of the system and the fact that the ventilator-lung assembly cannot be considered as a single-compartment model because of the presence of variable resistance represented by the upper airway. When NIV is initiated, the ventilator settings are determined empirically based on a clinical evaluation and diurnal blood gas variations. However, NIV is predominantly applied during sleep. Consequently, to assess overnight patient–machine 'agreement' and efficacy of ventilation, more specific and sophisticated monitoring is needed. The effectiveness of NIV might therefore be more correctly assessed by sleep studies than by daytime assessment. The most available and simple monitoring can be done from flow and pressure curves from the mask or the ventilator circuit. Examination of these tracings can give useful information to evaluate if the settings chosen by the operator were the right ones for that patient. However, as NIV allows a large range of ventilatory parameters and settings, it is mandatory to have information about this to better understand patient–ventilator interaction. Ventilatory modality, mode of triggering, pressurisation slope, use or not of positive end expiratory pressure and type of exhalation as well as ventilator performances may all have physiological consequences. Leaks and upper airway resistance variations may, in turn, modify these patterns. This article discusses the equipment available for NIV, analyses the effect of different ventilator modes and settings and of exhalation and connecting circuits on ventilatory traces and gives the background necessary to understand their impact on nocturnal monitoring of NIV.